The genetics of vascular incidents associated with second-generation antipsychotic administration. Issue 1 (January 2014) - Cocchi, Enrico; Drago, Antonio; Ronchi, Diana de; Serretti, Alessandro
<x xml:space="preserve">Abstract</x> Second-generation antipsychotics (SGA) have been associated with risk of stroke in elderly patients, but the molecular and genetic background under this association has been poorly investigated. The aim of the present study was to prioritize a list of genes with an SGA altered expression in order to characterize the genetic background of the SGA-associated stroke risk. Genes with evidence of an altered expression after SGA treatments in genome-wide investigations, both in animals and men, were identified. The Genetic Association Database (GAD) served to verify which of these genes had a proven positive association with an increased stroke risk, and alongwith it each evidence was tested and recorded. Seven hundred and forty five genes had evidence of a change of their expression profile after SGA administration in various studies. Nine out of them have also been significantly related to an increased strokes risk. We identified and described nine genes as potential candidates for future genetic studies aimed at identifying the genetic background of the SGA-related stroke risk. Further, we identify the molecular pathways in which these genes operate in order to provide a molecular framework to understand on which basis SGA may enhance the risk for stroke.